ANÁLISE FISIOLÓGICA E MOLECULAR EM Rhizophora mangle: RESPOSTAS AO ESTRESSE SALINO EM CONDIÇÕES DE CAMPO - Lopes, Dielle Meire de Santana (2019)
The mangrove ecosystem is highly productive, however, it is constantly subject to environmental stressors, which include salinity and elevated temperatures. The aim of the present study was to investigate the physiological and molecular bases of salt tole